Sporadic Fundic Gland Polyps with Dysplasia or Carcinoma: A Literature Review - Wataru Sano; Yasushi Sano (New Horizons in Medicine and Medical Research Vol. 9, 2022)
Fundic gland polyps (FGPs) are the most frequent gastric polyps and have long been thought to be benign lesions with limited malignant potential, except in the setting of familial adenomatous polyposis. However, the prevalence of FGPs has risen in recent years, paralleling the widespread and frequent use of proton pump inhibitors (PPIs). There have been a few reports of sporadic FGPs with dysplasia or carcinoma (FGPD/CAs) so far. In this review, we aimed to evaluate the clinical and endoscopic characteristics of sporadic FGPD/CAs and propose a management strategy of sporadic FGPs. The majority of patients with sporadic FGPD/CAs were middle-aged women on PPI medication who were not infected with Helicobacter pylori (H. pylori). The majority of sporadic FGPD/CAs were sessile and tiny, with a mean size of 5.4 mm, and occurred in the gastric body. During white light observation, the sporadic FGPs with cancer displayed redness, irregular surface structure, depression, or erosion, and irregular microvessels on the lesion surface during magnification narrow-band imaging. Furthermore, even with dysplasia, sporadic FGPs are likely to proceed slowly to malignancy. As a result, patients with sporadic FGPs do not require frequent endoscopy. If endoscopic findings other than conventional FGPs are found, regardless of their size, histological investigation is required. The prevalence of FGPs is projected to rise in the future, owing to the widespread and frequent use of PPIs and the decreasing H. pylori infection rate. It is currently unknown whether FGPD/CAs will increase at the same rate as FGPs. However, the patterns of these lesions suggest that they should be studied more in the future.